Air Quality Management in Poland - World Bank (World Bank, Washington, DC, 2019)
Despite significant efforts to reduce polluting air emissions, during and after the economic transition in the 1990s, Poland remains home to many of the most polluted cities in the European Union (EU). This report examines the nature and magnitude of ambient air pollution (AAP) in Poland. It provides estimates of the health burden, and economic cost associated with the health impacts, of ambient air pollution i.e., particulate matter (PM) both at national and regional or voivodeship levels in Poland. It also explores the roles of various sources of air pollution emissions on ambient air quality in Poland. With emphasis on the critical residential sector, this report analyses the likely impacts of national and EU legislative scenarios on future pollution emissions and ambient air quality in Poland. In addition, the report performs a demonstrative cost-benefit analysis of selected interventions to reduce AAP in residential and transport sectors and from point sources in the voivodeships that bear the heaviest burden of the impacts of AAP. Institutional factors that affect the effectiveness of ambient air quality management are discussed. Finally, policy recommendations for air pollution prevention, reduction and abatement are presented. The current study estimates that 25,280 - 44,811 deaths were caused by ambient PM2.5 pollution in Poland in 2016. The analysis applied two methodologies: (i) the approach from the 2016 Global Burden of Disease study; and (ii) the approach used by the EEA in their 2018 study. GBD studies analyze the health risks attributable to environmental factors, for different years, for most countries by linking environmental factors with the burden of disease attributable to them. Consistent with the GBD methodology, the analysis in this chapter applies a conservative approach by calculating premature, age-specific mortality from five diseases - ischemic heart disease, stroke, COPD, lung cancer, lower respiratory illness, that are directly linked to PM pollution. By contrast, the EEA approach calculates all-cause or non-accidental mortality (i.e., all deaths excluding poisoning, suicide and war), and assumes a linear relationship between mortality and PM concentration for population above age 30. The morbidity health burden is estimated in this report using HRAPIE recommended methodology (WHO, 2013) that focuses on acute bronchitis for children, chronic bronchitis for adults, cardiovascular and respiratory hospital admissions and lost work days caused by PM air pollution.